Utilization of waste from refined lemongrass for producing mosquito repellent. Issue 1 (January 2021) - Rusnanda, R; Ramadhini, M; Putra, W S; Asmaidi,
Abstract: Because of its geographical location, South Aceh Regency has many natural resources, one of which is fragrant lemongrass. As it is known, citronella is processed and produced into essential oils. In the production process, waste is produced in the form of solid waste and liquid waste. Usually, the waste is left and becomes a problem for the environment around the distillery. The purpose of this study was to make a mosquito repellent by utilizing citronella processing waste. This research is using the experimental method. This experimental method examines the effect of certain treatments on others under certain conditions. Three samples will be tested for combustion. The results of this study from each sample with a variable initial burning time. The first test kills mosquitoes. The durability of mosquito repellent is sample 3 is the best sample for making mosquito repellent from the use of citronella distillation waste seen from the burn test. The conclusion from this study, the waste produced by citronella distillation can be used as a basic ingredient in making mosquito repellent because there are active compounds contained in citronella waste capable of killing mosquitoes.